Population-Based Psychiatric Comorbidity in Children and Adolescents With Autism Spectrum Disorder: A Meta-Analysis - Mutluer, Tuba; Aslan Genç, Herdem; Özcan Morey, Aslihan; Yapici Eser, Hale; Ertinmaz, Beliz; Can, Merve; Munir, Kerim (Frontiers in Psychiatry, 2022)
Psychiatric comorbidity in autism spectrum disorder (ASD) is a subject of critical scientific importance, affecting the quality of life, prognosis, and functional outcomes. The prevalence of psychiatric disorders vary considerably according to variables such as index subject characteristics, study setting, sampling frame, diagnostic methods, used as well as country of origin. To date, most studies comprise clinical or treatment referral samples in tertiary care or subjects enrolled in clinical trials and genetic cohort collections. Such samples carry the potential for overestimation of both the frequency and severity of psychiatric comorbidity. A systematic literature search was performed using PubMed and Web of Science databases restricted to population-based study publications in the English between May 1, 2015, and May 31, 2020. A comprehensive keyword list was generated to investigate co-occurrence of psychiatric disorders in children and adolescents with ASD. A wide range of DSM-5 based disorders such as anxiety, mood, ADHD, intellectual disability/intellectual developmental disorder, eating/feeding, gender dysphoria and sleep-wake disorders were assessed. Initial search revealed a total of 1674 articles after removal of duplicates. Two independent researchers conducted a parallel-blinded screening process to identify the eligible studies based on titles and abstracts; 39 studies were analyzed in the current review. The main findings show prevalence estimates of 22.9 % (95 % CI: 17.7- 29.2) for intellectual disability; 26.2% (22-31) for attention-deficit hyperactivity disorder; 11.1% (8.6-14.1) for anxiety disorders; 19.7% (11.9-30.7) for sleep disorders; 7% (5.2- 9.3) for disruptive disorders; 2% (1.3- 3.1) for bipolar disorders; 2.7% (1.8- 4.2) for depression; 1.8% (0.4–8.7) for obsessive-compulsive disorder; and 0.6% (0.3–1.1) for psychosis. Psychiatric comorbidity in population-based studies is lower than in clinical and referred samples. However, our results also indicate that the frequency of psychiatric comorbidity in children and adolescents with ASD in the population context is considerable, without the influence of referral bias implicit in clinical and treatment samples. There is a need for better targeted diagnostic tools to detect psychiatric comorbidity in children and youth in future population based studies, as an essential component in providing care as well as new insights into the nature and mechanisms of its underlying associations.